A Stretchable Yarn Embedded Triboelectric Nanogenerator as Electronic Skin for Biomechanical Energy Harvesting and Multifunctional Pressure Sensing. Issue 43 (6th September 2018) - Dong, Kai; Wu, Zhiyi; Deng, Jianan; Wang, Aurelia C.; Zou, Haiyang; Chen, Chaoyu; Hu, Dongmei; Gu, Bohong; Sun, Baozhong; Wang, Zhong Lin
Abstract: Flexible and stretchable physical sensors capable of both energy harvesting and self‐powered sensing are vital to the rapid advancements in wearable electronics. Even so, there exist few studies that can integrate energy harvesting and self‐powered sensing into a single electronic skin. Here, a stretchable and washable skin‐inspired triboelectric nanogenerator (SI‐TENG) is developed for both biomechanical energy harvesting and versatile pressure sensing. A planar and designable conductive yarn network constructed from a three‐ply‐twisted silver‐coated nylon yarn is embedded into flexible elastomer, endowing the SI‐TENG with desired stretchability, good sensitivity, high detection precision, fast responsivity, and excellent mechanical stability. With a maximum average power density of 230 mW m −2, the SI‐TENG is able to light up 170 light‐emitting diodes, charge various capacitors, and drive miniature electronic products. As a self‐powered multifunctional sensor, the SI‐TENG is adopted to monitor human physiological signals, such as arterial pulse and voice vibrations. Furthermore, an intelligent prosthetic hand, a self‐powered pedometer/speedometer, a flexible digital keyboard, and a proof‐of‐concept pressure‐sensor array with 8 × 8 sensing pixels are successively demonstrated to further confirm its versatile application prospects. Based on these merits, the developed SI‐TENG has promising applications in wearable powering technology, physiological monitoring, intelligent prostheses, and human–machine interfaces. Abstract : A flexible, stretchable, washable, and multifunctional triboelectric‐based electronic skin obtained by embedding a planar and designable yarn electrode network into transparent elastomer is presented for both biomechanical energy harvesting and self‐powered pressure sensing. An energy harvester, physiological monitor, prosthetic hand, real‐time pedometer/speedometer, flexible digital keyboard, and tactile sensing array are successively demonstrated in order to confirm its versatile application prospects.